2016
DOI: 10.1590/s0100-204x2016001200007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among phenotypic and quality traits in indigenous and exotic accessions of linseed

Abstract: -The objective of this work was to evaluate the relationship among phenotypic and quality traits in a set of indigenous and exotic accessions of linseed (Linum usitatissimum). The experimental material consisted of 151 accessions of linseed belonging to landraces and cultivars collected from diverse agroecological zones. Five randomly chosen plants of each accession in each replicate were tagged, and data were recorded for the 12 following agronomic traits: days to flowering, days to maturity, plant weight, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(20 reference statements)
5
9
0
Order By: Relevance
“…In this study, the genotypic and phenotypic correlation coefficient was similar in directions, while in magnitude, genotypic correlations were mostly higher than corresponding phenotypic correlations "(Table 3)". The similar results [7], [10], [25] were obtained that genotypic correlation coefficients were higher than their respective phenotypic correlation coefficients for most of the characters. A study by [26], [27] has revealed that genotypic correlations are higher because of environment had a small role in the expression of the traits, which suggests an inherent association between these traits at the genetic level.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, the genotypic and phenotypic correlation coefficient was similar in directions, while in magnitude, genotypic correlations were mostly higher than corresponding phenotypic correlations "(Table 3)". The similar results [7], [10], [25] were obtained that genotypic correlation coefficients were higher than their respective phenotypic correlation coefficients for most of the characters. A study by [26], [27] has revealed that genotypic correlations are higher because of environment had a small role in the expression of the traits, which suggests an inherent association between these traits at the genetic level.…”
Section: Resultssupporting
confidence: 77%
“…Other important agronomic traits such as flowering time, plant height, plant branching, and lodging resistance may also indirectly affect yield through various physiological mechanisms [6], [8], allowing crop phenology and plant architecture to be adapted to regional growing conditions, thus avoiding yield and quality losses [9]. Knowledge of association between yield and its attributes obtainable through estimation of genotypic and phenotypic correlation helps to formulate plant breeding strategies to develop suitable genotypes [10], [11]. The positive correlation between major yield components, breeding strategies would be very effective but on the reverse, selection becomes very difficult [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports are available about the direct and indirect effects of various oil quality traits. Chauhan et al (2008) who reported high to moderate negative effects of palmitic, stearic, oleic, linoleic, linolenic and eicosenoic on erucic acid in Indian mustard varieties, and Siddiqui et al (2016) who reported the direct and indirect effect of various quantitative traits on oil quality traits in linseed. From the path analysis for genotypic correlation of OY with agro-morphological and oil traits (Table 5), it was revealed that small positive direct effect was observed for most of the traits that could be due to a weaker correlation of causative traits on OY (the effect).…”
Section: Resultsmentioning
confidence: 99%
“…Path analysis, also known as standardized partial-regression coefficient, partitions the correlation coefficients into direct and indirect effects and thereafter allows the separation of direct influence of each trait on yield from the indirect effects caused by mutual association among the traits themselves (Garcia del Morel et al, 2003). In agriculture, path analysis has been extensively used by breeders to assist in the identification of traits that are useful as selection criteria to improve crop yield (dos Santos et al, 2014;Mihretu et al, 2014;Sincik and Goksoy, 2014;Ranjbar et al, 2015;Khan et al, 2016;Siddiqi et al, 2016). Although considerable literature is available on correlation and path analysis in other foliage crops (Kaul et al, 1996;Young et al, 2000;Carpici and Celik 2010;Abel et al, 2017), a limited amount of work has been conducted in Chenopodium spp.…”
Section: Introductionmentioning
confidence: 99%